PEREMPUAN PEMULUNG DI TEMPAT PEMBUANGAN SAMPAH SEMENTARA KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Nurita Marito; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted on Scavenger Women in the Temporary Landfill  District Payung Sekaki Pekanbaru City. The purpose of this study is to find out how scavenger women play and to find out how the family economy of scavengers women. This study uses descriptive qualitative research methods. The subjects in this study were 5 people. Informant determination technique is by using purposive sampling technique. Purposive sampling is the taking of subjects by setting specific traits that are in accordance with the purpose of the research so that it is expected to answer the research problems. Researchers use observation and interview techniques in data collection. The theory used is the theory of economic sociology put forward by Damsar namely the concept of actors, economic actions, barriers to economic action, economic and community relations, application of methods. The result of this study is that scavenger women work as scavengers due to low economic factors. Scavenger women will go to the Temporary Dump every day with the aim of collecting the remains of food that will be used as pig food that they keep and will collect used goods that they will sell monthly. Before female scavengers go scavenging they will do homework first.The total income of a scavenger woman's family a month is 2,700,000 to 5,200,000. The spending that a scavenger woman's family has to spend a month ranging from 2,700,000 to 5,000,000. Until now the life of the scavenger family can be fulfilled well as well as the school of his son is still running.Keywords: Scavenger Women, Economic Situation